EVALUATING ACADEMIC SUPPORT SERVICE QUALITY IN DISTANCE LEARNING: A FUZZY-SERVQUAL APPROACH TO STUDENT SATISFACTION - Junianto, Mochammad Bagoes Satria (Department of Informatics Engineering, 2026)
The quality of academic support services is pivotal to student success and retention in distance education. This study evaluates the service quality of the Distance Learning Skills Training (PKBJJ) at Universitas Terbuka using the Fuzzy-SERVQUAL approach. A parallel 22-item SERVQUAL instrument was administered to 100 students to capture Expectations (E) and Perceptions (P) across five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Linguistic judgments on a 1–5 Likert scale were mapped to triangular fuzzy numbers (TFN), aggregated, and defuzzified (centroid) to obtain crisp scores for E and P; gaps were computed as P−E at both item and dimension levels. Findings show negative gaps across all dimensions, indicating services do not fully meet student expectations. Priority deficits were observed in Reliability (gap ≈ −0.038) and Responsiveness (≈ −0.0127), followed by Tangibles (≈ −0.0092), while Assurance (≈ −0.0060) and Empathy (≈ −0.0010) performed comparatively better but still below expectations. The results provide an actionable improvement map emphasizing process consistency, timely responses, and incremental enhancement of facilities, while maintaining strengths in assurance and empathy. Methodologically, the integration of fuzzy logic with SERVQUAL demonstrates better sensitivity to subjective and ambiguous appraisals common in distance learning contexts, yielding more representative and decision-ready metrics for quality improvement. Keywords: Service Quality; Fuzzy-SERVQUAL; Student Satisfaction; Distance Learning; Gap Analysis; Universitas Terbuka